Parade on Steadman Ave. for the July 4th celebration, Nome, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Shows dogfight blocking band members on the street. Caption on image: "Parade coming down Steadman Ave., Nome. July 4, 1901." Original image in Hegg Album 5, page 36. Original photograph by Eric A. Hegg 1833; copied by Webster and Stevens 365.A